2021
DOI: 10.3390/polym13172963
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Solubility and Absorption of Nifedipine Using Solid Solution: Correlations between Surface Free Energy and Drug Dissolution

Abstract: Ternary solid solutions composed of nifedipine (NDP), amino methacrylate copolymer (AMCP), and polysorbate (PS) 20, 60, or 65 were prepared using a solvent evaporation method. The dissolution profiles of NDP were used to study the effect of the addition of polysorbate based on hydrophilic properties. A solid solution of NDP and AMCP was recently developed; however, the dissolution of NDP was <70%. In the present study, polysorbate was added to improve the dissolution of the drug by altering its hydrophilici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Since C 0 (suspension) (A-B) is correlated to the aqueous solubility of curcumin, this suggests that the apical cellular uptake of curcumin can be affected by solubility. This view was further supported by other published studies, which found a positive correlation between the concentration of the drug dissolved in the donor compartment and the in vitro apical cellular drug uptake of Caco-2 cells [ 89 , 90 ].…”
Section: Discussionsupporting
confidence: 74%
“…Since C 0 (suspension) (A-B) is correlated to the aqueous solubility of curcumin, this suggests that the apical cellular uptake of curcumin can be affected by solubility. This view was further supported by other published studies, which found a positive correlation between the concentration of the drug dissolved in the donor compartment and the in vitro apical cellular drug uptake of Caco-2 cells [ 89 , 90 ].…”
Section: Discussionsupporting
confidence: 74%
“…During the past half a century, polymers have acted as a backbone role to support the fast developments of pharmaceutics [1][2][3][4][5][6][7][8], particularly the dosage forms for drug delivery [9][10][11][12][13][14][15][16]. The numbers in which natural and synthetic polymers are introduced into this interdisciplinary field is always increasing [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…As a popular electrohydrodynamic atomization (EHDA) method, electrospinning is similar to electrospraying in taking advantage of the easy interactions between working liquids and higher voltage electrostatic energy [56][57][58][59][60][61][62]. Their differences lie in the following: (1) the working fluids utilized in electrospinning often have a higher concentration and related viscosity than those exploited during electrospraying, and correspondingly (2) the products from electrospinning are fibers, whereas those from electrospraying are particles [63][64][65][66][67]. With either electrospinning or electrospraying, the functional ingredients can be co-dissolved with the polymeric matrices to experience the working processes for generating the desired polymer-based composites in a single step and a straightforward manner.…”
Section: Introductionmentioning
confidence: 99%